Pertanggungjawaban Pidana Perusahaan Shopee Atas Pelanggaran Tindak Pidana Merek (Study Kasus Pemalsuaan Produk Oleh Brand Hamlin) - Theresia Sinta Debora Sinaga (INVENTION: Journal of Intellectual Property Law, 2025)
The aim of this research is to determine the form of criminal responsibility of the Shopee marketplace for brand violations committed by sellers. The research method used is a normative research type. Using a statutory approach, conceptual approach and case approach. Sources of legal materials consist of primary legal materials, secondary legal materials and tertiary legal materials. The technique for collecting legal materials uses library research techniques. Using qualitative descriptive legal material analysis techniques, namely data obtained after being compiled systematically, and then analyzed in the form of descriptions. Based on the description of the research results and discussion in this research, it shows that regarding acts of infringement of the same brand, it is basically regulated in article 100 paragraph 1 of Law number 20 regarding brands and geographical indications. criminal responsibility related to the criminal acts that the author is reviewing, that the Shopee Company cannot be held responsible because Shopee is only a place for buying and selling transactions for sellers and consumers, but Shopee in this case can provide responsibility for incidents of brand infringement, responsibility for Shopee goods is not in the form of replacement in the form of physical, but Shopee's responsibility in the form of actions taken on seller accounts including: Deletion and blocking of registered accounts, restrictions on seller accounts, suspension and termination of accounts.